Alpha-amylase Inhibition and Brine Shrimp Lethality Activities of Nine Medicinal Plant Extracts from South-West Nigerian Ethnomedicine. Issue 4 (1st October 2016) - Ogbole, Omonike Oluyemisi; Aliu, Latifat Olabimpe; Abiodun, Oyindamola Olajumoke; Ajaiyeoba, Edith Oriabure
ABSTRACT: Acanthospermum hispidum, Alchornea laxiflora, Calyptrochilum christyanum, Heliotropicum indicum, Holarrhena floribunda, Ipomoea asarifolia, Nauclea diderrichii, Piper guineense, and Tetracera scandens were extracted into methanol and screened for the availability of alpha-amylase inhibitors. Plant extracts' toxicity was determined by brine shrimp lethality assay (BSLA). The most active plant, Nauclea diderichii, was fractionated into four solvent systems ( n -hexane fractions, ethyl acetate, dichloromethane, and n -butanol) and tested. All the extracts showed varying degrees of alpha-amylase inhibitory activity. N. diderrichii with IC50 = 248.30 ± 0.27 µ g.mL –1 had the highest inhibitory activity, while its butanol fraction with IC50 = 137.8 µ g.mL –1 had activity comparable to the standard α -amylase inhibitor acarbose (IC50 = 177.50 ± 0.42 µ g.mL –1 ). LC50 values for BSLA ranged from 11.35 to 1, 127.50 µ g.mL –1, with T. scandens being the most toxic with 11.35 µ g.mL –1 and N. diderrichii the least toxic with 1, 127.50 µ g.mL –1 .